How organizational learning affects the performance of SMEs: the case of information and communication technology companies in Malaysia - Zandi Pour Joopari, GholamReza; Sulaiman, Mohamed; Naysary, Babak; Mohamed Salim, Islam (International center of Science Education and Academic Research for Scholars, 2013)
The aim of this research is to empirically test the relationship between organizational learning and organizational performance in SMEs in the ICT industry in Malaysia. The focus of this study is to determine whether organizational learning lead to better organizational performance. This study was conducted in a sample of 278 SMEs in Malaysia. The hypotheses in this study were developed to examine the relationship between organizational learning (OL) and organizational performance (OP). To conduct the analysis we made use of Analysis of Moment Structure (AMOS 18.0) and Statistical Package for Social Sciences (SPSS 17.0). The results support the hypotheses implying a positive relationship between OL and OP. Several implications for management and policy are also discussed in light of the findings of this study.